PELATIHAN PEMBUATAN BIOGAS DARI KOTORAN SAPI DI DESA PONDOK KELAPA - I Nyoman Candra; Elvinawati Elvinawati; Amrul Bahar (Universitas Bengkulu, 2018)
The People of Pondok Kelapa mostly work as farm laborers, fishermen and farmers. People are still using raw wood fuel in cooking that has a negative impact in terms of health. LPG fuel is actually good for cooking, but it is relatively expensive. For that need to look for alternative fuels made from materials that are easy to obtain. This service activities such as training for making biogas from cow dung in the village of Pondok Kelapa. Biogas is a mixture of methane and carbon dioxide gas derived from anaerobic fermentation of organic substrates. In this activity, firstly conducted a survey and preparation. Furthermore held counseling, and the last is a core activities including the tool installation and biogas production. This activity produces biogas which initially resulted in a rather small flame. But after his gas collected, the gas produced is large enough. From these activities, the village of Pondok Kelapa succeeded in making biogas from manure. Keywords: biogas, cow manure, fermentation, anaerobic